Polymer selective laser curing for integrated optical switches - Gil-Valverde, Manuel; Cano-García, Manuel; Delgado, Rodrigo; Zuo, Tianyi; Otón, José Manuel; Quintana, Xabier; Geday, Morten Andreas (Photonics Letters of Poland, 2017)
A simple in-layer electro optical switch has been prepared by selectively curing a photocurable optical polymer with a UV laser. The core of the device is a NOA-81 multimode waveguide grown by selective laser curing. The cladding is a positive calamitic liquid crystal, which allows tunability and switching of the waveguide by external driving electric signals. The effective refractive index in the guide changes upon switching the liquid crystal. Depending on the geometry, this setup leads to an electrooptical modulator or a switch between two levels of transmitted light. Full Text: PDF References T. Ako, A. Hope, T. Nguyen, A. Mitchell, W. Bogaerts, K. Neyts, and J. Beeckman, "Electrically tuneable lateral leakage loss in liquid crystal clad shallow-etched silicon waveguides", Opt. Express 23, 2846 (2015). CrossRef K. Kruse, C. Middlebrook, "Laser-direct writing of single mode and multi-mode polymer step index waveguide structures for optical backplanes and interconnection assemblies", Photon. Nanostruct. - Fundamentals and Appl. 13, 66 (2015). CrossRef A. Günther, A.B. Petermann, M. Rezem, M. Rahlves, M. Wollweber, and B. Roth, European Conf. Lasers and Electro-Optics - European Quantum Electronics Conference, Munich, Germany (2015). C. Florian, S. Piazza, A. Diaspro, P. Serra, M. Duocastella, "Direct Laser Printing of Tailored Polymeric Microlenses", ACS Appl. Mater. Interfaces, 8(27), 17028 (2016). CrossRef F. Costache, M. Blasl, "Optical switching with isotropic liquid crystals", Opt. Photonik 6, 29 (2011). CrossRef M. Cano-Garcia, R. Delgado, T. Zuo, M.A. Geday, X. Quintana, Jose M. Otón, 16th OLC Topical Meeting on the Optics of Liquid Crystals, Sopot, Poland (2015). S. Ishihara, H. Wakemoto, K. Nakazima, Y. Matsuo, "The effect of rubbed polymer films on the liquid crystal alignment", Liq. Cryst. 4(6), 669 (1989). DirectLink